Development of microsatellite markers for Dimorphandra mollis (Leguminosae), a widespread tree from the Brazilian cerrado - Souza, Helena A. V.; Collevatti, Rosane G.; Lemos‐Filho, José P.; Santos, Fabrício R.; Lovato, Maria Bernadete (American journal of botany, 2012)
• Premise of the study: Microsatellite markers were developed for Dimorphandra mollis (Leguminosae), a widespread tree in the Brazilian cerrado (a savanna‐like vegetation). • Methods and Results: Microsatellite markers were developed from an enriched library. The analyses of polymorphism were based on 56 individuals from three populations. Nine microsatellite loci were polymorphic, with the number of alleles per locus ranging from three to 10 across populations. The observed and expected heterozygosities per locus and population ranged from 0.062 to 0.850 and from 0.062 to 0.832, respectively. • Conclusions: These microsatellites provide an efficient tool for population genetics studies and will be used to assess the genetic diversity and spatial genetic structure of D. mollis.